The linker between the D3 and A1 domains of vWF suppresses A1‐GPIbα catch bonds by site‐specific binding to the A1 domain. (27th July 2013) - Tischer, Alexander; Cruz, Miguel A.; Auton, Matthew
Abstract: Platelet attachment to von Willebrand factor (vWF) requires the interaction between the platelet GP1bα and exposed vWF‐A1 domains. Structural insights into the mechanism of the A1‐GP1bα interaction have been limited to an N‐terminally truncated A1 domain that lacks residues Q 1238  −  E 1260 that make up the linker between the D3 and A1 domains of vWF. We have demonstrated that removal of these residues destabilizes quaternary interactions in the A1A2A3 tridomain and contributes to platelet activation under high shear (Auton et al ., J Biol Chem 2012;287:14579–14585). In this study, we demonstrate that removal of these residues from the single A1 domain enhances platelet pause times on immobilized A1 under rheological shear. A rigorous comparison between the truncated A1‐1261 and full length A1‐1238 domains demonstrates a kinetic stabilization of the A1 domain induced by these N‐terminal residues as evident in the enthalpy of the unfolding transition. This stabilization occurs through site and sequence‐specific binding of the N‐terminal peptide to A1. Binding of free N‐terminal peptide to A1‐1261 has an affinity K D = 46 ± 6 μ M and this binding although free to dissociate is sufficient to suppress the platelet pause times to levels comparable to A1‐1238 under shear stress. Our results support a dual‐structure/function role for this linker region involving a conformational equilibria that maintains quaternary A domain associations in the inactive state of vWF at low shear and an intra‐A1‐domain conformation that regulates the strength of platelet GP1bα‐vWF A1 domain associations in the active state of vWF at high shear.